GEOELECTRICAL SECTION OF THE BARGUZIN BAY OF LAKE BAIKAL ACCORDING TO GEORADAR AND RADIO IMPEDANCE SOUNDING DATA - Yu. B. Bashkuev; V. B. Khaptanov; M. G. Dembelov (Геодинамика и тектонофизика)
Electrical resistivity (electrical conductivity) of water and bottom soil of the Barguzin Bay was studied by radio impedance soundings in VLF/LF bands, and the measurements were analysed. The georadar sounding method was used to investigate dielectric permittivity of freshwater ice (dielectric constant is ε=3.4). We developed the technique of radio impedance sounding from the ice surface of Lake Baikal for measuring the electrical resistance of bottom soil in the water area, and applied this technique to a layered model of a medium with a base showing poor/good conductivity. Geoelectric models were constructed for the Barguzin Bay coast and the southern Lake Baikal. The geoelectrical section (GES) of the water area can be useful for earthquake forecasting from electromagnetic data, as well as for analysing the physical and chemical causes of the occurrence of ring structures on the ice surface of Lake Baikal.